2014
DOI: 10.1007/s12031-013-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Treatment Produces an Antinociceptive Response Phase and Inhibits Astrocyte Activation and Inflammatory Response in a Rat Model of Neuropathic Pain

Abstract: Hyperbaric oxygen (HBO) treatment has been proven to be a promising candidate for protection of the nervous system after acute injury in animal models of neuropathic pain. The purposes of this study were to examine the antinociceptive response phase induced by HBO treatment in a model of neuropathic pain and to determine the dependence of the treatment's mechanism of alleviating neuropathic pain on the inhibition of spinal astrocyte activation. Neuropathic pain was induced in rats by chronic constriction injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…6 Our previous study demonstrated the involvement of activated astrocytes in the generation of hyperalgesia. 7 Blocking the secretion of the proinflammatory chemokines or balancing the production of proinflammatory and anti-inflammatory cytokines has been found to attenuate pain hypersensitivity. 8 In light of these findings, the inflammatory response modulated by activated astrocytes appears to be an important event in the pathogenesis of neuropathic pain.…”
mentioning
confidence: 99%
“…6 Our previous study demonstrated the involvement of activated astrocytes in the generation of hyperalgesia. 7 Blocking the secretion of the proinflammatory chemokines or balancing the production of proinflammatory and anti-inflammatory cytokines has been found to attenuate pain hypersensitivity. 8 In light of these findings, the inflammatory response modulated by activated astrocytes appears to be an important event in the pathogenesis of neuropathic pain.…”
mentioning
confidence: 99%
“…HBO therapy was conducted as previously described 13. The chamber was filled with pure oxygen for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…13 Sections were probed with rabbit polyclonal anti-glial fibrillary acidic protein (anti-GFAP) primary antibody (1:1000 dilution; Dako, Copenhagen, Denmark). On the second day, the samples were incubated with goat anti-rabbit biotinylated secondary antibody (1:500 dilution; Beijing Zhongshan Golden Bridge Biological Technology Co. Ltd., China), followed by incubation in SABC complex (Vector Laboratories, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it inhibits astrocyte activation and inflammatory response [25]. HBO therapy involves the administration of 100% of oxygen at a pressure higher than 1 atmosphere (atm) at sea level [26] for times not shorter than 60 minutes as delineated by the European Consensus Conference on Hyperbaric Medicine held in Lille, France in 1994 [27].…”
Section: Introductionmentioning
confidence: 99%